The impact of corporate image on students’ satisfaction and loyalty - Abdullah, Zulhamri; Omar Ali, Siti Rapidah (Zes Rokman Resources, 2018)
Over the last few years, institutional image has become an important element to the competitiveness of higher education institutions. The increase in the number of both public and private higher education institutions (HEI) in Malaysia has resulted in the industry becoming relatively very competitive. The situation calls for HEIs to focus on establishing a strong corporate image by improving students’ satisfaction and loyalty. Thus, this study aims to examine the relationship between the students’ satisfaction and loyalty towards corporate image of UiTM Kuala Terengganu. A sample of 306 students was selected among undergraduate students at UiTM Kuala Terengganu. Descriptive analysis, Pearson correlation and multiple regressions were employed to achieve the objectives of the study. The findings of the study illustrate that, students’ satisfaction and loyalty were found to be significant drivers of the corporate image of UiTM Kuala Terengganu which students’ loyalty emerged as the main predictor. Research findings confirmed that the positive relationship between students’ satisfaction and loyalty towards corporate image of UiTM Kuala Terengganu. Indeed, a today’s University has to focus on stakeholder imperative as it found that students’ satisfaction and loyalty can give an impact to corporate image of this university. This will lead to building the corporate reputation of this institution. Based on these findings, implications and some recommendations are made for policy makers and also future studies.